Development of Geography Learning Media With Dieng Plateau Material to Support Grade X Students' Field Introduction - Eka Suci Anja Kusumawati; Muhammad Taufik Rahmadi (Universitas Lambung Mangkurat, 2025)
The 21st century demands interactive learning media that follow technological developments and student needs, but the number of interactive learning media is very limited, especially volcanism material that can support field introduction. This condition causes ineffectiveness in learning. Therefore, learning media is needed that accommodates student needs based on student learning styles, especially in field introduction. This study aims to develop Macromedia Flash-based learning media with Dieng Plateau material. The type of research used is Research and Development. The development procedure includes the stages of definition, design, development, and distribution. The data collection technique used is purposive random sampling. Data collection using a media suitability questionnaire by validation experts and product trials in schools which are divided into three stages. Data analysis techniques in this study were analyzed using qualitative assessments. Assessment data in the form of scores from media experts and students obtained through questionnaires were analyzed descriptively quantitatively with percentages and categorization. The results of the study indicate that geography learning media is suitable for use to support field introduction for grade X students. Recommendations for further research are the effectiveness of developing learning media in improving students' field introduction.